Development of orthotopic breast cancer and detection of nNav 1.5 serum antibody in syngeneic mouse model - Noor, Aina Akmal Mohd (2019)
The functions of voltage-gated sodium channels (VGSCs) are to propagate action potential mechanism in excitable cells and promote metastasis in cancer cells. VGSCs isoform, Nav1.5 in its splice variants, neonatal Nav1.5 (nNav1.5) is upregulated in protein level to mediate cancer cell migration and invasion particularly in metastatic breast cancer. nNav1.5 is a developmentally regulated gene – shown to be abundant in neonatal tissue but not in adult tissue and is classified as tumour associated antigen (TAA). However, no study has investigated the presence of antibody against nNav1.5 in breast cancer; patients or tumour model. Hence, this present study aimed to develop breast cancer mouse model from cultured murine breast carcinoma 4T1 cells and to detect nNav1.5 serum antibody using ELISA. 4T1 cells were inoculated orthotopically onto the subcutaneous mammary fat pad of BALB/c mice to produce a syngeneic model. The successfully mammary tumour development could be observed concurrently with significant weight loss, lethargic response and abnormal coat condition of the mice. Due to the increased size of the mammary tumour, the breast cancer mice reached its neoplasia endpoint at day 25 and humanely euthanised. The ELISA assessment of the animal serum revealed that nNav1.5 serum antibody was not detected in both normal and breast cancer mice. It was an interesting finding that both tested sera showed no significant difference despite the lungs of the mammary tumour mice exhibited white patches suggesting that metastasis via haematogenous route had occurred. The current findings suggest that the nNav1.5 serum antibody within breast cancer cells potentially depicted a masking effect and/or an escape mechanism Therefore, the findings obtained could have generate useful preliminary knowledge in regards to the behaviour of nNav1.5. However, future investigations should be put forward to further delineate the exact mechanism that lies behind these current findings.